Why Do Female Victims of Domestic Violence Rarely Report It? A Literature Review - Wahyudi, Fidela Dzatadini; Putra, Rizky Perdana Bayu; Irwan, Muhamad; Ariani, Relys Sandi; zulfaida, arini; Doroh, Gasper (International Journal of Sustainable Law, 2025)
Not only limited to individual decisions, it turns out that there are several things that can make female victims of domestic violence reluctant to report the violence they experienced. This study aims to analyze the causes why women victims of domestic violence are reluctant to report their cases. This literature study research found that cultural, gender, and social structure factors are one of the causes of women victims of domestic violence who are reluctant to report gender-based violence problems in the domestic sphere. In addition,  problems of legal culture and institutional capacity that are not yet gender-sensitive, such as limited training of apparatus, lack of integrated assistance services, and the risk of secondary victimization during the legal process strengthen the vulnerable position of victims of domestic violence, making women victims of domestic violence make the decision not to report the domestic violence they experience.